1. (-5/6).(-3/5)^2
(-5/6).(-9/25)
= (5/6) * (9/25)
= 45/150
= 3/10
2. 2022o -- 1/2
= 2022 * (-1/2)
= -2022/2
= -1011
3. (3/4 - 5/6)^2
= (9/12 - 10/12)^2
= (-1/12)^2
= 1/144
4. -3/4 * 12 / (-5) * (-25/6)
= -3/4 * 12 / 5 * 25/6
= (-3 * 3 * 5) / (4 * 5 * 6)
= -45/120
= -3/8
5. (-1/3)^2 : 5/9 + (-1)^3
= 1/9 : 5/9 + (-1)
= 1/9 * 9/5 - 1
= 1/5 - 1
= -4/5
6. 5/2 + 1/2 : (-3/4) * 4/9 - 4^2 - (-2)^3
= 5/2 + 1/2 * (-4/3) * 4/9 - 16 - (-8)
= 5/2 - 2/6 - 16 + 8
= 5/2 - 1/3 - 8
= (15 - 2 - 48) / 6
= -35/6
7. (-1/2 - 1/3)^2 : ((-5/36) - (-5/36)^0)
= (-3/6 - 2/6)^2 : ((-5/36) - 1)
= (-5/6)^2 : (-5/36 - 1)
= (25/36) : (-41/36)
= 25/36 * (-36/41)
= -25/41
8. (-6/7 + 3/7 : (-3)) - (2/5 + (-7/8)^0 + 3/5 : (-3/2))
= (-6/7 + 3/7 * (-1)) - (2/5 + 1 + 3/5 * (-2/3))
= (-6/7 - 3/7) - (2/5 - 2/3)
= -9/7 - (6/15 - 10/15)
= -9/7 - (-4/15)
= -9/7 + 4/15
= (-135/105 + 28/105)
= -107/105